Wakaf Properties Used As Guarantee For Debt Are Reviewed In Law Number 41 Of 2004 Concerning Wakaf And The Compilation Of Islamic Law - Farhan Asyhadi; Lia Amaliya; Ahmad Saprudin (Ilmu Hukum Prima (IHP), 2026)
Land is one of the most common objects used as collateral. Waqf will be valid as a continuous charity after the owner truly declares the assets he has donated to be public assets and he freezes his rights for the benefit of the community. The identification of the problem in this study is How is the view of Islamic Law and Law Number 41 of 2004 regarding waqf assets used as collateral for debt? As well as the Legal Consequences of waqf land used as collateral According to Law Number 41 of 2004 The methodology used in this study uses normative juridical, The conclusion of this study is based on Article 40 of Law Number 41 of 2004 concerning Waqf that waqf assets are prohibited from being used as collateral, confiscated, donated, sold, inherited, exchanged, transferred in other forms of transfer of rights. And in Article 225 of the Compilation of Islamic Law, objects that have been donated cannot be changed or used other than those intended in the waqf pledge. The agreement with collateral in the form of waqf land does not meet the requirements for a lawful cause, thus the agreement is null and void by law. The criminal provisions are regulated in Article 67 of Law No. 41 of 2004.